The Effect of The Square Drill Passing Trainning Method on the Passing Accuracy of IMFA Clubs ageds 15 Years - Anugerah Muhammad Afrizal; Purwono Sidik Permono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Football is one of the most populer sports in society and has many benefits. One of problems that occurs in football is passing because there are still mistakes when passing. The purpose of this study was to determine the effect of suare drill tranning on the passing ability of U-15 Indonesia Muda Football Academy players. This type of research is quantitative using one group pretest-posttest design. The population in this study were U-15 players of the Indonesia Muda Football Academy Club. The sampling technique used total sampling, namely all U-15 players were sampled as many as 12 players. The research data were analyzed descriptively quantitatively, the requirement test was normality and homogeneity test of data, and the T test using SPSS 26.00. Based on the table above, it can be concluded that the value of t=Low 3.973, this value is greater than t=Upper 2.527 or t=Low of 3.973 and the sig. The result (2-tailed) is 0.000<0.05. This means that there is a significant influence between the Square Drill Passing Trainning Method on the Passing Accuracy of the 15-Year-Old IMFA Club.